Characterisation of polymer cement mortar composites containing carbon fibre or auxetic fabric overlays and inserts under flexure. (10th November 2019) - Asad, Mohammad; Dhanasekar, Manicka; Zahra, Tatheer; Thambiratnam, David
Highlights: Polymer cement matrix (PCM) with and without fabric overlays/inserts characterised. Benefits of carbon fibre (CF) and auxetic fabrics (AF) to PCM investigated. CF overlayed/inserted specimens exhibited debonding and high peak load. AF overlayed/inserted specimens exhibited no debonding and high energy absorption. An elastic FE with contact nonlinearity predicted debonding in CF but not in AF. Abstract: An experimental investigation on the flexural response of polymer cement mortar matrix overlayed or inserted with carbon fibre or auxetic fabric layers subject to four levels of rates of loading (1–150 mm/min) is reported. Seventy-two specimens made from plain polymer cement mortar, composites with auxetic and carbon fibre fabric layers overlayed at the bottom and inserted at the mid-depth of the specimens were prepared and tested under four point bending. The failure mode including debonding, peak load, load-deflection behaviour, longitudinal strain at peak load, ultimate stage and energy dissipation are reported. All composite specimens exhibited higher peak load, longitudinal strain and energy dissipation in comparison to the plain polymer mortar specimens. Auxetic fabric composites exhibited increased energy dissipation and longitudinal strain at peak load without any sign of debonding. Carbon fibre composites, on the other hand, failed due to debonding at a lower longitudinal strain. A finite element model is presented to demonstrate the debonding tendencies observed in the experiments. Increase in rate of loading improved the performance of the auxetic fabric composites but reduced the energy dissipation of carbon fibre composites.